2023
DOI: 10.1002/pan3.10462
|View full text |Cite
|
Sign up to set email alerts
|

Institutional amnesia pushes fish spawning aggregations towards extirpation

Abstract: How institutions create and manage knowledge has been explored in the context of management and business science. However, little effort has been made to understand how, and why, these institutions forget what works or does not work, and no research in this field has been conducted in conservation or fisheries science. This paper examines the concept of institutional amnesia by focussing a lens on fish spawning aggregations and efforts to monitor and protect them in the Mesoamerican Reef. For over 20 years, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…We found that the exceptional increased availability of BSB during the warm regime of the 1980s and 1990s was not the norm for much of the last century. Shifting baselines and institutional amnesia can result in diminished expectations of what the size of a healthy aggregate spawner population should be, inadvertently resulting in less conservative, less effective, management measures (Fulton 2023).…”
Section: Discussionmentioning
confidence: 99%
“…We found that the exceptional increased availability of BSB during the warm regime of the 1980s and 1990s was not the norm for much of the last century. Shifting baselines and institutional amnesia can result in diminished expectations of what the size of a healthy aggregate spawner population should be, inadvertently resulting in less conservative, less effective, management measures (Fulton 2023).…”
Section: Discussionmentioning
confidence: 99%